2019
DOI: 10.36423/hexagro.v3i2.280
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Faktor-Faktor Motivasi Terhadap Kinerja Pegawai Di Pt. Bank Bni Syariah Cabang Jakarta Barat

Abstract: BNI Syariah sebagai Bank Umum Syariah berkomitmen untuk memenuhi dan menyempurnakan rencana pengembangan SDM dari waktu ke waktu untuk menunjang kinerja dan layanan yang terbaik kepada para stakeholder serta mewujudkan world class human capital. Hal ini tentunya menuntut adanya kinerja yang tinggi dari para pegawai untuk dapat melaksanakan tugas-tugas dengan baik. Usaha organisasi untuk meningkatkan produktivitasnya baik dalam aspek finansial maupun non finansial mengalami berbagai hambatan, salah satunya adal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…Hygiene factors and motivator factors affect employee performance, this is in line with research conducted by: (Pramono, 2007), (Setyaningsih et al, 2014), (Suhanda et al, 2015), (Dewi & Thendean, 2018), (Tapala, 2018), (Prabowo et al, 2018), (Suhardi, 2019), (Perwita, 2019), (Sekar Arumsari & Widowati, 2019), (Candana et al, 2020), (Ma'ruf & Chair, 2020), (Yulius, 2021) and (Hutagalung, 2022).…”
Section: The Influence Of Hygiene Factors and Motivating Factors On E...supporting
confidence: 78%
“…Hygiene factors and motivator factors affect employee performance, this is in line with research conducted by: (Pramono, 2007), (Setyaningsih et al, 2014), (Suhanda et al, 2015), (Dewi & Thendean, 2018), (Tapala, 2018), (Prabowo et al, 2018), (Suhardi, 2019), (Perwita, 2019), (Sekar Arumsari & Widowati, 2019), (Candana et al, 2020), (Ma'ruf & Chair, 2020), (Yulius, 2021) and (Hutagalung, 2022).…”
Section: The Influence Of Hygiene Factors and Motivating Factors On E...supporting
confidence: 78%
“…Pegawai adalah sebagai pelopor bergeraknya kegiatan dalam sebuah perusahaan (Nursaman & Sisdianto, 2020). Kinerja seorang pegawai yang efektif dan efisien merupakan sisi terbaik agar perusahaan terus beroperasional dengan maksimal (Perwita, 2019). Dalam dunia perbankan kinerja pegawai menjadi sorotan penting, sebagai perusahaan yang bergerak dalam pelayanan jasa bank harus bisa memiliki sumber daya manusia yang kompeten (Arifudin & Rusmana, 2020).…”
Section: Pendahuluanunclassified
“…In several previous studies that partially tested the effect of motivation on employee performance at Banks, such as Asmarazisa (2016) on Bank BTN BATAM employees; Marliani (2016) on employees of Bank BNI Karawang; Sajangbati (2016) on employees of Bank BNI Manado; Husain (2018) on employees of BNI BSD Branch;Tho'in (2018) on employees of BNI Syariah Surakarta branch; Santoso (2018) on employees of Bank BNI Pamulang; and Winata (2019) on employees of Bank BJB BSD branch all show that motivation can affect employee performance. The author only found research from Maheswari & Lutvy (2017) on employees of Bank Ekonomi Raharja Area Jakarta 5; Perwita (2019) for employees of Bank BNI Syariah West Jakarta Branch; and Malkan et al (2020) on Bank Mandiri KCP Palu Imam Bonjol employees who found that motivation did not affect the performance of Bank employees.…”
Section: Introductionmentioning
confidence: 98%